Influence of nitrogen source and rate on lettuce yield and quality. (14th March 2022) - Zandvakili, Omid R.; Barker, Allen V.; Hashemi, Masoud; Autio, Wesley R.; Etemadi, Fatemeh; Sadeghpour, Amir
Abstract: Organic fertilizers are significantly lower in N content than chemical fertilizers, yet they can offer opportunities for efficient N utilization in lettuce ( Lactuca sativa  L.) production. A 2‐yr split‐split plot trial was conducted in the growing seasons of 2018 and 2019 at South Deerfield, MA, to evaluate the effect of source and rate of N fertilizers on yield, and quality of two lettuce cultivars. Nitrogen sources including blood meal (BLM), dehulled soybean meal (DSM), dehydrated cow manure (DCM), and urea (URE) were the main plots. Nitrogen application rates of 0, 60, 120, and 180 kg N ha –1 were subplots and two lettuce cultivars with different morphological phenotypes of iceberg ('Mighty Joe') and leaf lettuce ('Bergam's Green') were sub‐subplots. Quadratic model explained lettuce yield response to N fertilizer rate, regardless of cultivar and N source. Among all N sources, DCM resulted in the least total N, nitrate‐N, ammonium‐N, and the lowest fresh lettuce yield (24.0 Mg ha –1 ) compared with URE (30.1 Mg ha –1 ), DSM (30.7 Mg ha –1 ) and BLM (28.7 Mg ha –1 ). Lettuce N requirement at maximum yield was 157.7, 171.4, 112.5, and 191.7 kg ha –1 for BLM, DSM, DCM, and URE, respectively. An increase in N application rate increased total N, nitrate‐N, and ammonium‐N but decreased agronomic efficiency and apparent N recovery. Incidence of lettuce tipburn and head decay was cultivar specific and was not influenced by N source. We concluded that DSM could be used as an organic fertilizer source that provides N similar to that of URE for lettuce production. Core Ideas: A quadratic model explained lettuce yield response to N fertilizer rate. Dehydrated cow manure had the lowest N use efficiency. Dehulled soybean meal performed similar to urea fertilizer. Incidence of lettuce tipburn and head decay was cultivar specific.